Ecological Crisis and Modern Cosmology: A Critique of the Materialist Paradigm and Reconstruction Through Islamic Conception - Alniatul Fadilah; Rahmi Syahriza; Nursa'idah Nursa'idah; Muhammad Syamsul Munir; Yongki Sutoyo; Muhammad Fahmi Amrullah (AL-TAHRIR, 2025)
The purpose of the study is to return to the conception of cosmology as something that is not only a natural material but also has an immaterial nature. This research used qualitative techniques based on the search bibliography. The concept of matter that developed during this period was influenced by the development of science. Initially, classical cosmology viewed the universe as a unity encompassing both physical (material) and non-physical (immaterial) aspects, including things considered sacred, such as God. The development of modern cosmology then separated its scientific approach from this sacred dimension. From there, the beginning happens crisis ecology begins with a paradigm shift. Therefore, shifting paradigms through revolutionary science allegedly contains problems that distance man from nature as well as cause damage to sustainable nature. Therefore, the research will discuss about shift in paradigm cosmology, modern science has resulted in crisis ecology, and will criticize as well as sit back to the problem with paradigm Islam. Researchers give a conclusion that crisis ecology today happens to leave from the crisis awareness man that not all matters must be measured with the material will, but there is more sacred that needs to be understood. Finally shift method view in the creation and natural universe makes the Conception of sacredness naturally lost, and the damage system that occurs today.